The effects of a 10-day altitude training camp at 1828 meters on varsity cross-country runners - Diebel, S. R.; Newhouse, I.; Thompson, D. S.; Johnson, V. B. K. (International Journal of Exercise Science, 2016)
Altitude training has been shown to alter blood lactate (BL) levels due to alterations resulting from acclimatization. This study aims to estimate the impact of altitude training on BL changes immediately following an incremental treadmill test and during recovery before and after 10-day altitude training at approximately 1828 meters. Eight varsity cross-country runners performed an incremental treadmill test (ITT), pre and post-altitude training. Resting and post-warm-up BL values were recorded. During ITT, heart rate (HR), oxygen saturation (SpO2), and time to exhaustion were monitored. BL was also measured post-ITT at 0, 2, 4, 6, and 8 minutes. The average of all BL values was higher following altitude intervention (8.8 ± 4.6 mmol/L) compared to pre-intervention (7.4 ± 3.3 mmol/L). These differences were statistically significant (t(6) = -2.40, p = .026). BL immediately (0 minutes) after the ITT was higher following the altitude intervention (13.6 ± 3.6 mmol/L) compared to pre-intervention (9.7 ± 3.8 mmol/L) and was statistically significant (t(7) = -3.30, p = .006). Average HR during the ITT was lower following the altitude intervention (176.9 ± 11.1 bpm) compared to pre (187 ± 9.5 bpm), these differences were statistically significant (t(28)= 18.07, p=p= <.001. Time to exhaustion was longer after the intervention, however was not statistically significant p = 0.13. These findings indicate that a 10-day altitude intervention at 1828 meters may benefit varsity cross-country runners. The higher post-exercise BL may be attributed to more anaerobic contributions. Lower HR may suggest a larger stroke volume and/ or more efficient O2 carrying capacity.